2004
DOI: 10.1002/food.200300428
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and angiotension‐converting enzyme inhibition capacities of various parts of Benincasa hispida (wax gourd)

Abstract: Vegetables and fruits have been shown to be good sources of antioxidants. Benincasa hispida (wax gourd) has been used in traditional Chinese medicine to treat hypertension and inflammation. The aims of this study were to investigate the abilities of antioxidation and inhibition of angiotensin-converting enzyme (ACE) activity of wax gourd pulp, core, seed, and peel prepared by different extraction methods. The fresh weights required to reach 50% inhibition of linoleic acid oxidation were higher in fresh extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…Antioxidants have been suggested to reduce oxidative damage including damage from lipid peroxidation, and therefore prevent various diseases such as diabetic complications (Lim, 2007), atherosclerosis, cancer, aging, and inflammation (Huang, Huang, Tso, Tsai, & Chang, 2004). Some in vitro and in vivo studies conducted on Kundur fruit revealed that its juice and extract has antioxidant activity especially on human tissues like liver and brain Roy, Ghosh, & Guha, 2007).…”
Section: Antioxidant Activitymentioning
confidence: 96%
See 3 more Smart Citations
“…Antioxidants have been suggested to reduce oxidative damage including damage from lipid peroxidation, and therefore prevent various diseases such as diabetic complications (Lim, 2007), atherosclerosis, cancer, aging, and inflammation (Huang, Huang, Tso, Tsai, & Chang, 2004). Some in vitro and in vivo studies conducted on Kundur fruit revealed that its juice and extract has antioxidant activity especially on human tissues like liver and brain Roy, Ghosh, & Guha, 2007).…”
Section: Antioxidant Activitymentioning
confidence: 96%
“…According to Bhalodia et al (2009), angiotensin-2 stimulates intracellular formation of reactive oxygen species (ROS) such as superoxide anion and hydrogen peroxide that led to kidney damage. Huang et al (2004) demonstrated that the inhibition of ACE activity by Kundur fruit may be due to its high phenolic contents and superoxide dismutase activity. This may provide the pharmacological basis for its long time uses in the treatment of high blood pressure in traditional Chinese medicine.…”
Section: Antioxidant Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…Amaranthus tricolor was reported to have cyclooxygenase and human tumour cell growth inhibitory activities [5] . Benincasa hispida was found to have antiulcerogenic activity, bronchospasm inhibition activity, antioxidant and angiotensin converting enzyme inhibition capacity, hypoglycemic and antihyperglecemic activity [6][7][8][9][10] , Corchorus olitorius was found to have antibacterial activity, antioxidant and antidiabetic effects, anti-angiogenic effects, anorectic activity, glucose and lipid lowering activity [10][11][12][13][14] . anticonvulsion and antisteroidogenic activity , cytotoxic and antimalarial activity [15][16][17][18] for the source of histamine release inhibitors and phenolic antioxidants [19,20] .…”
Section: P E E R R E V I E W Abstractmentioning
confidence: 99%